Toxinotyping and Sequencing of Clostridium difficile Isolates from Patients in a Tertiary Care Hospital of Northern India - Singh, Meenakshi; Vaishnavi, Chetana; Mahmood, Safrun; Kochhar, Rakesh (Frontiers in Medicine, 2017)
Background: Clostridium difficile is an important cause of infectious colitis among hospitalized patients across the globe. The pathogenic potential of C. difficile in producing significant morbidity and mortality is mainly due to production of toxins A and B. The outbreaks of C. difficile infection (CDI) are due to changes in the genetic sequences of the organism. There is hardly any molecular study reported on the prevalent types of C. difficile strains in India. Toxinotyping and sequencing of locally circulating C. difficile isolates from patients presenting to our tertiary care center of North India were done. Materials and methods: C. difficile strains (n=174) isolated from 1110 fecal samples from patients with suspected CDI were subjected to toxinotyping and partial sequencing of tcdA and tcdB genes. Comparison of nucleotide sequences with reference C. difficile 630 strain using BLAST was made and translated into corresponding amino acid sequences by ExPASy. Results and discussion: Of 174 C. difficile isolates, 121 were toxigenic, belonging to toxinotype 0 (n=76) and VIII (n=45). Partial sequencing of toxin genes using bioinformatics approaches revealed changes in toxin A sequences of five (50%) C. difficile isolates, but the translated nucleotide sequences showed substitution in only three of them. No variation was seen in the toxin B nucleotide sequences. Inter-strain variations were found in the clinical C. difficile isolates in our region. Conclusion: PCR amplified toxigenic genes followed by sequencing can help to identify genetic changes and pathogenicity of varied collection of C. difficile isolates.